2005
DOI: 10.1111/j.1365-2591.2005.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo study of the adhesion of an epoxy‐based sealer to human dentine submitted to irradiation with Er : YAG and Nd : YAG lasers

Abstract: An increase in frequency, independent of power settings, of the lasers used in this study increased adhesion of an epoxy-based root canal sealer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
2
36

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 21 publications
3
83
2
36
Order By: Relevance
“…Furthermore, the test's loading closely simulates clinical stresses as the applied load is perpendicular to the dentinal tubules 17) . Therefore, the push-out test allows accurate specimen standardization 18) and generates fewer stresses at the bonding interface during sample preparation than conventional tensile and shear bond testing 19) . On the other hand, it has been stated that the results of a push-out test can be affected by some variables such as specimen orientation, different root canal diameters and different plunger sizes 17) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the test's loading closely simulates clinical stresses as the applied load is perpendicular to the dentinal tubules 17) . Therefore, the push-out test allows accurate specimen standardization 18) and generates fewer stresses at the bonding interface during sample preparation than conventional tensile and shear bond testing 19) . On the other hand, it has been stated that the results of a push-out test can be affected by some variables such as specimen orientation, different root canal diameters and different plunger sizes 17) .…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, epoxy resin-based sealers showed higher adhesion to root canal dentin and deeper penetration into the dentinal tubules than glass ionomer-and ZnOE-based sealers 25,[27][28][29] . This meant that retention of the fi lling material might be improved by mechanically locking it into place, hence reinforcing root canal dentin to increase its fracture resistance.…”
Section: Effect Of Root Canal Sealers On Fracture Resistance Of Rootfmentioning
confidence: 99%
“…3,12 These techniques enable visualization of the distribution of root filling materials, such as gutta-percha and sealer, inside the canal. 3 However, the sealer bond strength is related to its ability to remain adhered to the root dentin walls, 20 and this property is important in static and dynamic situations. In static circumstances, the adhesion eliminates spaces that allow infiltration of fluids into the sealer/dentin interface.…”
Section: Discussionmentioning
confidence: 99%